2014
DOI: 10.1007/s11295-014-0821-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of Pyrus accessions of Indian Himalayan region based on morphological and SSR markers

Abstract: Genetic diversity and phylogenetic relationships among 48 pear accessions belonging to six species were determined using 23 morphological traits and 20 simple sequence repeat (SSR) primers. To assess the genetic diversity, data on morphological (both quantitative and qualitative) traits were recorded during 2010-2012 using standard pear descriptors. It was observed that the traits ratio of fruit length to diameter, persistency of calyx on mature fruits and fruit surface and pulp texture were important in detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…DNA markers offer more accurate information on genetic diversity, as they are rarely influenced by environmental factors of a region (Sharma et al 2008 ). Furthermore, SSR markers specifically possess many desirable useful properties which makes them most preffered DNA markers (Powell et al 1996 ; Rana et al 2015 ; Sharma et al 2015 ). The newly developed SSR markers appeared valuable in detecting diversity in studied germplasm of T. terrestris .…”
Section: Discussionmentioning
confidence: 99%
“…DNA markers offer more accurate information on genetic diversity, as they are rarely influenced by environmental factors of a region (Sharma et al 2008 ). Furthermore, SSR markers specifically possess many desirable useful properties which makes them most preffered DNA markers (Powell et al 1996 ; Rana et al 2015 ; Sharma et al 2015 ). The newly developed SSR markers appeared valuable in detecting diversity in studied germplasm of T. terrestris .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these markers, SSRs, in particular, have been widely used for genetic relationship and diversity studies given their hyper-variability, co-dominant nature, prevalent locus-specificity, and random genome-wide distributions. A large set of SSR markers has been developed from Japanese and European pear [ 16 – 18 ] and subsequently used for genetic characterization and identification of different Pyrus species [ 19 22 ]. In addition, SSR markers present a high transferability between related species and genera.…”
Section: Introductionmentioning
confidence: 99%
“…3). A similar study was conducted by Rana et al (2015) where they observed that the ratio of length and diameter of the fruits, persistent calyx in mature fruit, fruit surface and texture of the flesh were important in detecting the morphological variations between pear species.…”
Section: Discussionmentioning
confidence: 68%